Interaction between warfarin and cannabis. Issue 1 (6th November 2018) - Damkier, Per; Lassen, Dorte; Christensen, Mette Marie Hougaard; Madsen, Kenneth Grønkjær; Hellfritzsch, Maja; Pottegård, Anton
Abstract: Delta‐9‐tetrahydrocannabinol (THC), the main psychoactive cannabinoid in cannabis, may inhibit the cytochrome P450 enzyme CYP2C9. Consequently, cannabis use might infer a risk of drug‐drug interaction with substrates for this enzyme, which includes drugs known to have a narrow therapeutic window. In this study, we describe a case report of a 27‐year‐old man treated with warfarin due to mechanical heart valve replacement who presented with elevated international normalized ratio (INR) value (INR = 4.6) following recreational cannabis use. We conducted a review of the available literature, using the PubMed and EMBASE databases while following PRISMA guidelines. Following screening of 85 articles, three eligible articles were identified, including one in vitro study and two case reports. The in vitro study indicated that THC inhibits the CYP2C9‐mediated metabolism of warfarin. One case study reported of a man who on two occasions of increased marijuana use experienced INR values above 10 as well as bleeding. The other case study reported of a patient who initiated treatment with a liquid formulation of cannabidiol for the management of epilepsy, ultimately necessitating a 30% reduction in warfarin dose to maintain therapeutic INR values. The available, although sparse, data suggest that use of cannabinoids increases INR values in patients receiving warfarin. Until further data are available, we suggest patients receiving warfarin be warned against cannabis use.